The history of Vartan, and of the battle of the Armenians - Eghishē, Saint, Vardapet, -480 (My University, 1830)
History of Vardan and the Armenian War (or History of Vartan, and of the Battle of the Armenians) is a 5th-century text by Yeghishe (Eghishe) chronicling the rebellion of Christian Armenians against the Zoroastrian Sassanid Empire. It details the struggle for religious freedom, focusing on the 451 AD Battle of Avarayr led by Vardan Mamikonian
Containing an account of the religious wars between the Persians and Armenians
History of the religious wars between the Persians and Armenians by Elisæus, Bishop of the Arnadunians
Translated from the Armenian by C.F. Neumann. - London : Printed for the Oriental Translation Fund, and sold by J. Murray, 1830. - XXIV, 111, [5] p. ; 27 cm.
Keywords: Mamikonian, Vardan Saint, -451; Avarayr, Battle of, Iran, 451; Armenia-History-428-640